Relationship between depression, anxiety, and attendance at pelvic-floor muscle training sessions - Phil Reed (Physiotherapy, 2023)
Objectives: Psychological comorbidities are associated with non-attendance for pelvic-floor muscle training (PFMT) appointments and non-engagement with ongoing treatment. However, little direct work has examined the precise relationship between these variables. Design: A prospective observational study of consecutively referred women patients with Pelvic-floor Dysfunction. Patients were assessed at intake for age, BMI, pelvic symptoms (measured by the Queensland Pelvic Symptom Scale), and anxiety and depression (measured by the Hospital Anxiety and Depression Scales). Setting: A women’s health physiotherapy outpatient unit of a metropolitan hospital. Participants: 433 consecutively-referred women with pelvic-floor dysfunction (PFD). Interventions: Six sessions of PFMT, lasting over a period of 6 months. Main outcome measures: Attendance at PFMT sessions was the outcome, and was related to intake patient age, BMI, pelvic symptoms, as well as anxiety and depression. Results: Psychological symptoms of depression and anxiety predicted attendance at PFMT sessions, over and above physical symptoms. Depression was the key predictor of non-attendance, with anxiety having a more complex relationship with attendance. There were few differences between these psychological variables and the different types of PFD, or between type of PFD and PFMT attendance. Conclusions: The findings add to the literature suggesting that consideration of patients’ psychological state is important when designing treatment-regimes.